2008
DOI: 10.1007/s00442-008-1127-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of global environmental change: long-term CO2 and nitrogen treatments influence offspring growth response to elevated CO2

Abstract: Global environmental changes can have immediate impacts on plant growth, physiology, and phenology. Long-term effects that are only observable after one or more generations are also likely to occur. These transgenerational effects can result either from maternal environmental effects or from evolutionary responses to novel selection pressures and are important because they may alter the ultimate ecological impact of the environmental change. Here, we show that transgenerational effects of atmospheric carbon di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
1
56
0
Order By: Relevance
“…Increased N deposition changes soil acidity and macronutrient availability (Vitousek et al 1997, Aber et al 1998) which alters plant biomass allocation, phenology, fitness, and competitive interactions (Cleland et al 2006, Clark and Tilman 2008, Lau et al 2008). The effects of N deposition on plant growth and soil fertility can affect ecosystem net primary production, plant diversity, and global climate via effects on carbon cycling (Vitousek et al 1997, Gruber 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Increased N deposition changes soil acidity and macronutrient availability (Vitousek et al 1997, Aber et al 1998) which alters plant biomass allocation, phenology, fitness, and competitive interactions (Cleland et al 2006, Clark and Tilman 2008, Lau et al 2008). The effects of N deposition on plant growth and soil fertility can affect ecosystem net primary production, plant diversity, and global climate via effects on carbon cycling (Vitousek et al 1997, Gruber 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased germination (Farnsworth and Bazzaz 1995;Andalo et al 1996) and seed weight (Wulff and Alexander 1985) have been reported for other plant species growing in elevated CO 2 , although enhanced seed weight has also been reported (Steinger et al 2000;Miyagi et al 2007). Although most studies point to CO 2 -induced effects on seed characteristics as the mechanism through which intergenerational differences occur, it may also be possible that these effects are driven by genetic changes in a plant's response to elevated CO 2 (Ward and Kelly 2004;Lau et al 2008;Leakey et al 2009). Genetic changes often occur over multiple generations, but recent epigenetic studies have shown that heritable changes in gene expression and function can also occur from one generation to the next.…”
Section: Multigeneration Responsesmentioning
confidence: 97%
“…A number of studies have now been published which show that a variety of plant species show intergenerational differences in their responses to conditions of elevated CO 2 (Andalo et al 1998;Bezemer et al 1998;Huxman et al 1998Huxman et al , 2001Derner et al 2004;Lau et al 2008). In our study, seed weight and germinability of P. annua were both significantly lower for plants grown in conditions of elevated CO 2 , and this might-at least partly-explain the differences observed in CO 2 responsiveness during the succeeding generation.…”
Section: Multigeneration Responsesmentioning
confidence: 99%
See 2 more Smart Citations